Genetic Variations in Metallothionein Genes and Susceptibility to Hypertensive Disorders of Pregnancy: A Case-Control Study - Wei, Shudan; Yu, Xiangyuan; Wen, Xiaolan; Zhang, Min; Lang, Qi; Zhong, Ping; Huang, Bo (Frontiers in Genetics, 2022)
Background: The involvement of oxidative stress in the pathological process of hypertensive disorders of pregnancy (HDP) gives rise to the interest in exploring the association of genetic variations in anti-oxidant metallothionein (MT) genes with the HDP susceptibility. Methods: Seventeen single nucleotide polymorphisms (SNPs) in MT genes were selected to conduct genotyping based on a case-control study consisting of 371 HDP cases (pregnancy with chronic hypertension (66), gestational hypertension (172), and preeclampsia, or preeclampsia superimposed on chronic hypertension (133)) and 479 controls. The association between SNPs in MTs and the risk of HDP was estimated with unconditional logistic regression analysis and further test with the false positive report probability (FPRP) procedure. The joint effects of the SNPs were assessed by using the haplotype analysis. Results: After adjustment for age and pre-pregnancy body mass index (pre-BMI) in the logistic regress analysis and followed by the FPRP test, the genetic variation rs10636 (OR=0.46, 95% CI: 0.30∼0.71 for GG vs. CC, P=0.000; OR=0.48, 95% CI: 0.32∼0.73 for GG vs. CG/CC, P=0.001) in MT2A was associated with gestational hypertension. Other 4 SNPs, i.e., rs11076161 (OR=1.89, 95% CI: 1.35∼2.63 for GG vs. GA/AA, P=0.000) in MT1A, rs7191779 (OR=1.54, 95% CI: 1.11∼2.13 for CC vs. CG/GG, P=0.010) in MT1B, rs8044719 (OR=0.57, 95% CI: 0.40∼0.80 for GT vs. GG, P=0.001) in MT1DP, and rs8052334 (OR=1.52, 95% CI:1.10∼2.11 for TT vs. TC/CC, P=0.012) in MT1B were significantly associated with the susceptibility of HDP. The haplotype analysis among 11, 10, 10, and 7 SNPs in MT (MT1A, MT2A, MT1M, MT1B, MT1DP) genes showed that 8 (A-C-G-T-C-G-A-G-C-G-C, OR=4.559; A-C-T-C-C-C-A-G-C-G-C, OR=5.777; A-C-T-T-C-G-A-G-C-G-C, OR=4.590; G-A-T-C-C-G-C-G-G-C-C, OR=4.065; G-A-T-C-G-C-C-G-G-C-C, OR=4.652; G-A-T-T-C-C-C-G-G-C-C, OR=0.404; G-C-T-C-C-C-A-G-G-C-C, OR=1.901; G-C-T-T-C-C-A-G-G-C-C, OR=3.810), 5 (C-G-A-T-C-A-C-C-G-G, OR=2.032; C-G-A-T-C-G-C-C-G-G, OR=2.077; G-A-C-T-C-A-C-C-T-G, OR=0.564; G-G-A-G-C-A-C-C-G-G, OR=5.466; G-G-A-T-T-A-G-C-G-G, OR=0.284), 5 (A-C-G-T-C-G-A-G-C-C, OR=2.399; A-C-T-C-C-C-C-T-G-G, OR=0.259; G-A-T-C-C-C-C-G-G-C, OR=1.572; G-A-T-C-G-C-C-G-G-C, OR=0.001; G-C-T-C-G-C-A-G-G-C, OR=2.512), and 5 (A-C-T-C-C-C-G, OR=0.634; G-A-G-C-C-C-G, OR=4.047; G-A-T-T-G-C-G, OR=0.499; G-C-G-T-C-A-G, OR=7.299; G-C-T-C-C-A-G, OR=1.434) haplotypes were significantly associated with PCH, GH, PE/PESCH, and HDP, respectively. Conclusion: These variant MT alleles and their combination patterns may be used as genetic markers for predicting the HDP susceptibility.